Structural and Functional Hippocampal Correlations in Environmental Enrichment During the Adolescent to Adulthood Transition in Mice - Manno, Francis A. M.; Kumar, Rachit; An, Ziqi; Khan, Muhammad Shehzad; Su, Junfeng; Liu, Jiaming; Wu, Ed X.; He, Jufang; Feng, Yanqiu; Lau, Condon (Frontiers in Systems Neuroscience, 2022)
Environmental enrichment is known to induce neuronal changes; however, the underlying structural and functional factors involved are not fully known and remain an active area of study. To investigate these factors, we assessed enriched environment (EE) and standard environment (SE) control mice over a 30-day period using structural and functional MRI methods. Naïve adult male mice (n = 30, ≈20 g, C57BL/B6 J, post-natal day 60 initial scan) were divided into SE and EE groups and scanned before and after a 30-day period. Structural analyses included volumetry based on manual segmentation as well as diffusion tensor imaging (DTI). Functional analyses included seed-based-analysis (SBA), independent component analysis (ICA), amplitude of low-frequency fluctuation (ALFF), and fractional ALFF (fALFF). Structural results indicated that environmental enrichment led to an increase in the volumes of cornu ammonis 1 (CA1) and dentate gyrus. Structural results indicated changes in radial diffusivity and mean diffusivity in the visual cortex and secondary somatosensory cortex after EE. Furthermore, SBA and ICA indicated an increase in rsfMRI functional connectivity in the hippocampus. Using parallel structural and functional analyses, we have demonstrated coexistent structural and functional changes in the hippocampal subdivision CA1. Future research should map alterations temporally during environmental enrichment to investigate the initiation of these structural and functional changes.